Intravitreal anti-VEGF therapy for choroidal neovascularisation secondary to pathological myopia: 4-year outcome - Ruiz-Moreno, JM (2014)
OBJECTIVE: To report the visual outcome after 4-year follow-up in a series of highly myopic eyes with choroidal neovascularisation (CNV) treated with antivascular endothelial growth factor (anti-VEGF) drugs. METHODS: A retrospective, non-randomised, multicentre, consecutive, interventional case series study was performed. 92 highly myopic eyes with subfoveal CNV were treated with intravitreal injection (IVI) of anti-VEGF. The initial protocol (1 vs 3 injections) was dictated by surgeons' preferences and followed by an as-needed monthly regime. Best-corrected visual acuity (BCVA) was evaluated at baseline and then monthly. The primary aim was to analyse BCVA changes. The effect of age, spherical equivalent (SE) and treating drug were evaluated as secondary objectives. RESULTS: The mean age of the patients was 57 years (SD 14, range 30-93). The mean number of letters read was 46.1 (SD 16.8, range 5-70) at baseline, 55.5 (SD 18.6, range 10-85) at 12 months, 50.1 (SD 20.1, range 5-82) at 24 months, 54.2 (SD 21.9, range 2-85) at 36 months and 53.1 (SD 22.5, range 1-83) at 48 months (p=0.000, initial vs 12, 24 and 36 months; p=0.01 initial vs 48 months; Student t test for paired data). The mean total number of IVI was 4.9 (SD 5.4, range 1-29). SE and treating drug had no influence on the final visual outcome and number of injections required. CONCLUSIONS: Intravitreal bevacizumab and ranibizumab are effective therapies and show similar clinical effects in highly myopic CNV. Visual acuity gain is maintained at 4-year follow-up.